2014
DOI: 10.2478/s13382-014-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases are strongly associated with sickness absences in a sample of Italian public employees

Abstract: Objectives: Data on the prevalence of chronic diseases and their relationship with sickness absence in the Italian public employees are rather scarce. Therefore, in the first place, we assessed the distribution of chronic diseases in the employees of the University of Ferrara. As a next step, we investigated the possible associations between each chronic disease and cumulative days of all-cause sickness absence, and finally we investigated the odds ratio of each single chronic disease on sickness absence. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
3
12
0
1
Order By: Relevance
“…Until now, studies analyzing the impact of chronic health conditions on different occupational outcomes have generally examined a single, specific health condition [4244]. Few have considered the effect of multiple coexisting chronic conditions on occupational outcomes such as sickness absence and work performance [45, 46], and none have focused on the course of work functioning over time. Measuring multimorbidity may help identify workers with a CMD who return to work and still may need special attention.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, studies analyzing the impact of chronic health conditions on different occupational outcomes have generally examined a single, specific health condition [4244]. Few have considered the effect of multiple coexisting chronic conditions on occupational outcomes such as sickness absence and work performance [45, 46], and none have focused on the course of work functioning over time. Measuring multimorbidity may help identify workers with a CMD who return to work and still may need special attention.…”
Section: Discussionmentioning
confidence: 99%
“…Casimirri and co-workers found an association between sickness absence days and the presence of ≥2 chronic diseases in a cross-sectional study among 514 sicklisted and not sick-listed Italian workers (41). Likewise, Ubalde-Lopez found that the greater the number of health conditions, the higher the risk of sickness absence in a cross sectional study of 72 370 Spanish workers (7).…”
Section: Sundsturp Et Almentioning
confidence: 99%
“…Findings from a separate analysis of the effects of MPNs on work productivity in respondents of the Living with MPNs survey demonstrated a significant negative correlation between symptom burden and work productivity [ 7 ]. Studies in other symptomatic diseases, such as arthritis, psychiatric disorders, and gastrointestinal diseases, also show significantly higher numbers of sickness absences compared with the general population [ 16 , 17 ]. These findings underscore the prominent role that symptoms play in affecting the functional ability for everyday life and work among patients with MPNs.…”
Section: Discussionmentioning
confidence: 99%